A Gain-of-Function Mutation in TRPA1 Causes familial episodic pain syndrome (2010)
ABSTRACT: Human monogenic pain syndromes have provided important insights into the molecular mechanisms that underlie normal and pathological pain states. We describe an autosomal-dominant familial episodic pain syndrome characterized by episodes of debilitating upper body pain, triggered by fasting and physical stress. Linkage and haplotype analysis mapped this phenotype to a 25 cM region on chromosome 8q12–8q13. Candidate gene sequencing identified a point mutation (N855S) in the S4 transmembrane segment of TRPA1, a key sensor for environmental irritants. The mutant channel showed a normal pharmacological profile but altered biophysical properties, with a 5-fold increase in inward current on activation at normal resting potentials. Quantitative sensory testing demonstrated normal baseline sensory thresholds but an enhanced secondary hyperalgesia to punctate stimuli on treatment with mustard oil. TRPA1 antagonists inhibit the mutant channel, promising a useful therapy for this disorder. Our findings provide evidence that variation in the TRPA1 gene can alter pain perception in humans.